2014
DOI: 10.2135/cropsci2013.08.0550
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Breeding, and Marker‐Assisted Selection for Verticillium Wilt Resistance in Cotton

Abstract: Verticillium wilt (VW), caused by the soil‐borne fungus Verticillium dahliae Kleb., is one of the most destructive diseases in Upland cotton (Gossypium hirsutum L.) production in the U.S. and worldwide. Development of VW‐resistant cultivars remains the only economic option for controlling the disease. The objective of this review was to summarize the progress in screening methods, resistance sources, and genetics, quantitative trait locus (QTL) mapping, marker‐assisted selection (MAS) and breeding for VW resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
84
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 82 publications
(212 reference statements)
1
84
0
2
Order By: Relevance
“…More than 100 QTLs related to VW have been detected on most of the 26 tetraploid cotton chromosomes except on chromosomes c6, c10, c12, and c18 (Zhang et al, 2014a,b, 2015). In this study, VW QTLs with minor contributions to the observed PV were detected on these four chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…More than 100 QTLs related to VW have been detected on most of the 26 tetraploid cotton chromosomes except on chromosomes c6, c10, c12, and c18 (Zhang et al, 2014a,b, 2015). In this study, VW QTLs with minor contributions to the observed PV were detected on these four chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…For the strain V991, 3 VW QTLs have been previously mapped on c9, c17, and c23 using a RIL population from Prema × 86-1 (Ning et al, 2013) and 2 QTLs on c6 and c21 using a F2:3 population (Zhang et al, 2014a). In this study, VW strain V991 resistance QTLs were identified on c1, c5, c10, c14, c15, c17, c20, c22, c25 for DI and on c2-c4, c7, c10, c11, c14, c15, c17, c21, and c22 for DInc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations